14 UMPSA students participate in Introduction to Underwater Welding Programme - Siti Rabiatull Aisha, Idris (UMPSA, 2023)
BANGI, 21 August 2023 – A total of 14 Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) students recently participated in the Introduction to Underwater Welding Programme in Bangi, Selangor.